Guidelines for the Prevention and Treatment of Chronic Hepatitis B (Version 2022) - You, Hong; Wang, Fu-Sheng; Li, Taisheng; Xu, Xiaoyuan; Sun, Yameng; Nan, Yuemin; Wang, Guiqiang; Hou, Jinlin; Duan, Zhongping; Wei, Lai; Jia, Jidong; Zhuang, Hui (Medicine (Baltimore), 2023)
Abstract To facilitate the achieving of the goal of "eliminating viral hepatitis as a major public health threat by 2030" set by the World Health Organization, the Chinese Society of Hepatology together with the Chinese Society of Infectious Diseases (both are branches of the Chinese Medical Association) organized a panel of experts and updated the guidelines for prevention and treatment of chronic hepatitis B in China (version 2022). With the support of available evidence, this revision of the guidelines focuses on active prevention, large-scale testing, and expansion of therapeutic indication of chronic hepatitis B with the aim of reducing the hepatitis B-related disease burden.